Assessing the impact of apnea duration on the relationship between obstructive sleep apnea and hearing loss. - Yong Seok Jo; Jeon Mi Lee (PLoS ONE)
Objectives The relationship between obstructive sleep apnea (OSA) and hearing loss (HL) remains uncertain. This study aimed to investigate the relationship between OSA and HL, and to identify which factors play a key role. Methods A retrospective review was conducted of 90 subjects diagnosed with OSA. These subjects underwent overnight polysomnography (PSG) and pure-tone audiometry at a single institution from February 2014 to November 2023. Hearing evaluations involved the comparison of OSA subjects with a non-OSA group, identified through national data utilizing the STOP-BANG questionnaire (SBQ) and age-sex 1:1 matching. Subsequently, individuals with OSA were categorized into HL and non-HL groups. Comparisons were made to ascertain differences in PSG parameters, followed by regression analysis to assess their actual impact. Results The OSA group exhibited elevated hearing thresholds across all frequencies compared to the non-OSA group. Furthermore, classification of OSA subjects into the HL and non-HL groups revealed a statistically significant increase in apnea duration in the HL group for all-frequency and high-frequency cases (p = 0.038, 0.006). Multiple linear regression analysis, adjusting for age and sex, revealed a significant influence of apnea duration on HL in both all-frequency and high-frequency cases (ß = 0.404, p = 0.002; ß = 0.425, p = 0.001). Conclusion These findings underscore the significant association between OSA and reduced auditory function, with apnea duration standing out as a crucial factor contributing to hearing loss. Our results suggest that prolonged apnea duration may be a marker of chronic hypoxic damage in patients with OSA, further clarifying its potential role in the development of hearing loss.